A Pragmatic Study of Presupposition in the Lyrics of NIKI’s Song “Around” - Febriani, Kartika Nida; Kurniawan, Olivia Rachel; Ibadurrahman, Hanif; Bila, Salsa (Lexeme : Journal of Linguistics and Applied Linguistics, 2026)
This study examines the use of presupposition in the song Around from NIKI’s 2018 debut album Zephyr. Using Yule’s (1996) classification, which includes existential, factive, lexical, structural, non-factive, and counterfactual presuppositions, this research identifies the presuppositional triggers found in the lyrics and interprets their implied meanings within the song’s narrative context. A qualitative descriptive approach was used to analyze how these presuppositions shape the emotional and communicative nuances of the lyrics. The findings show that several types of presupposition appear in Around, with existential and factive presuppositions occurring most frequently. These presuppositions reveal implicit meanings related to longing, emotional conflict, and personal reflection. Overall, the study concludes that presupposition serves as an important linguistic strategy in NIKI’s songwriting because it enriches the expressive depth of the lyrics and guides listeners toward the underlying emotional narrative.